Relative Standing: A Framework for Understanding Departures of Acquired Executives - Hambrick, Donald C.; Cannella, Albert A. (Academy of Management Journal, 1993)
Prior attempts to explain the departure rates of the executives of acquired firms, primarily through strategic and economic logics, have yielded limited results. This study drew on the concept of relative standing, or local social status, to explain why some acquired executives depart. Using a dynamic modeling methodology to study 430 executives in 97 acquired firms, we present evidence to support this new perspective on executive departure. Implications and directions for future research on postacquisition outcomes are discussed.